Expanded graphite for thermal conductivity and reliability enhancement and supercooling decrease of MgCl2⋅6H2O phase change material. (June 2018) - Song, Zichen; Deng, Yong; Li, Jinhong; Nian, Hongen
Graphical abstract: Highlights: MgCl2 ·6H2 O/EG composite PCMs show the superior thermal transfer ability. 83.33 wt.% of MgCl2 ·6H2 O encapsulated in composite PCM was obtained. EG and nucleating agents decreased the supercooling degree. Abstract: Expanded graphite (EG) is considered as a promising supporter for phase change material (PCM) due to its unique porous structure and excellent heat transfer ability. In the study, EG with different mass fractions (9 wt.%, 13 wt.%, 16.67 wt.%, and 20 wt.%) was respectively blended with MgCl2 ·6H2 O. The thermal conductivity data of composite PCMs with 9 wt.%, 13 wt.%, 16.67 wt.%, and 20 wt.% of EG was respectively measured to be 0.942 W/m K, 1.053 W/m K, 1.354 W/m K and 1.658 W/m K. DSC analysis showed that 16.67 wt.% of EG decreased the degree of supercooling by 29.4 °C and that the addition of 3.0 wt.% SrCO3 further decreased the degree of supercooling by 17.9 °C. The maximum encapsulation weight percentage of MgCl2 ·6H2 O reached 83.33 wt.% after 30 phase change cycles without significantly reducing its latent heat value, exhibiting the relatively stable thermal reliability.